Association Between the Health Locus of Control and Medication Adherence: An Observational, Cross-Sectional Study in Primary Care - Gerland, Hanna-Maria E.; Prell, Tino (Frontiers in Medicine, 2021)
Background: Medication nonadherence is an important healthcare issue and a common problem. Many predictors of nonadherence have been found in different settings and cohorts. Objective: Evaluate the impact of the health locus of control (HLC) on unintentional/intentional nonadherence in primary care. Methods: In this observational, cross-sectional study, 188 patients (mean age 63.3 +/- 14.9 years) were recruited from three primary care practices in Jena, Germany, over four months. The study assessed demographic data, self-reported adherence (German Stendal adherence to medication score, SAMS), HLC, and depression. Results: According to the SAMS total score, 44 (27.5%) were fully adherent, 93 (58.1%) were moderately nonadherent, and 23 (14.4%) were clinically significantly nonadherent. The most common reasons for nonadherence were forgetting to take the medication or lacking knowledge about the prescribed medication. Multiple linear regression revealed that adherence was good in people with external HLC and poor in internal HLC. In particular, intentional nonadherence was positively associated with internal HLC and negatively with fatalistic external HLC. Depression had a negative influence on both intentional and unintentional nonadherence. Conclusion: HLC is an independent predictor of medication nonadherence and is a promising target for interventions that enhance adherence.